2007
DOI: 10.1203/pdr.0b013e31809871f1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Control of VEGF and TGF-β1 Gene Polymorphisms in Childhood Urinary Tract Infection and Vesicoureteral Reflux

Abstract: ABSTRACT:We investigated whether genetic polymorphisms of vascular endothelial growth factor (VEGF) and transforming growth factor-␤1 (TGF-␤1), potential candidate genes in the pathogenesis of urinary tract infection (UTI) and vesicoureteral reflux (VUR), are associated with the susceptibility to UTI and VUR, and renal scarring. We recruited 89 controls and 86 UTI and 58 VUR children. The UTI group was subdivided into two groups according to renal scarring. Two polymorphisms of VEGF and three of TGF-␤1 genes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 40 publications
1
57
1
Order By: Relevance
“…Nonetheless, in the present patient, we hypothesize that TIAF1 haploinsufficiency may have perturbed an alternative, RET-independent HSCR pathway, namely the TGF-b-signalling pathway, thus increasing not only the risk of developing intestinal aganglionosis but also, based on the control that TGF-b variants seem to exert on the pathogenesis of urinary tract infection and vesicoureteral reflux, 24 the risk of developing VUR. In particular,…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Nonetheless, in the present patient, we hypothesize that TIAF1 haploinsufficiency may have perturbed an alternative, RET-independent HSCR pathway, namely the TGF-b-signalling pathway, thus increasing not only the risk of developing intestinal aganglionosis but also, based on the control that TGF-b variants seem to exert on the pathogenesis of urinary tract infection and vesicoureteral reflux, 24 the risk of developing VUR. In particular,…”
mentioning
confidence: 75%
“…VUR has often been reported to be associated with TGF-b signal-dependent Mowat -Wilson syndrome (38%) and TGF-b1 polymorphisms have been recently shown to be associated with the susceptibility to VUR. 5,24 On the other hand, the RET gene plays a critical role in kidney development and it has been found involved in isolated congenital anomalies of the kidney. 25 Considering that, like HSCR, vesico-ureteral reflux is a genetically heterogeneous trait which may occur as a result of the complex inheritance, we suggest that contemporary defects in the two pathways (decreased RET expression and TIAF1 haploinsufficiency) may be critical for the onset of vesico-ureteral reflux in our proband and that these different pathways may be involved in other cases of either syndromic or isolated vesico-ureteral reflux or renal malformations.…”
mentioning
confidence: 99%
“…Kowalewska-Pietrzak et al 30 reported that TT genotype carriers of À509 T/C polymorphism was a risk factor for renal scarring in primary vesicoureteral reflux (VUR), and was also associated with susceptibility to congenital uropathy. Yim et al 31 reported that TGF-b1 C-509T, G-800A, and T869C polymorphisms could be genetic markers of the process of urinary tract infection and VUR. Solari et al 32 reported that TGF-b1 À509 T/C gene polymorphisms may be at higher risk for reflux nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…The first studies describing the role of the 460 TϾC polymorphism were conducted on Asians (20,21). Their results indicated that the frequency of the T allele was about 75%, and the frequency of the C allele was about 25%.…”
Section: Discussionmentioning
confidence: 99%